SOSIALISASI ANALISA KELAYAKAN FINANSIAL PADA SISWA SMA NEGERI 3 JEMBER - Hilmi, Ahmad Iqbal; Mayanda, Bernicha Dwivani; Prayogi, Fahrur; P, Vania Yanuarita P; N, Yodick Febrian; Kusuma, Moch Nur Hadi; H, Prames Aulia Sukma; Aprilia, Aura Denis; Rizqi, Putra Dwi; Ekawardani, Naeda Tamara; Gunasti, Amri; Priyono, Pujo; Kuryanto, Totok Dwi; Abadi, Taufan; Hazmi, Muhammad (Universitas Mataram, 2024)
Today's economic and technological advancements have made the term “investment” widely recognized. Basically, investment is the result of various parties working together to achieve mutually beneficial cooperation. Education about the capital market can be carried out to various ages, one of which is millennials, namely high school / vocational high school students. Every child needs to be economically literate, and schools are institutions that can provide good knowledge and skills to children. Service on financial feasibility analysis is carried out to educate students in analyzing financial feasibility. This service was carried out at Jember Public High School 3 which is located in Tegal Besar, Kaliwates sub-district, Jember Regency. This service was carried out by presenting material from service members to students who had previously conducted a pre-test first. After the presentation of the material students were also asked to fill in the post-test that had been provided. From the service activities that have been carried out, it can be concluded that this service activity has expanded students' knowledge of engineering economics in analyzing financial feasibility.